Association of Surgeons in Training conference: Bournemouth 2017. (April 2018) - Williams, A.P.; Harries, R.L.; Mohan, H.M.
Abstract: The Association of Surgeons in Training (ASiT) is a professional body and registered charity working to promote excellence in surgical training for the benefit of junior doctors and patients alike. The Association provides support at both regional and national levels throughout the United Kingdom and Republic of Ireland. Originally founded in 1976, ASiT is independent of the National Health Service (NHS), Surgical Royal Colleges, and specialty associations. The 2017 Annual Conference in Bournemouth brought together over 700 delegates for a diverse educational weekend with numerous expert guest speakers. With a theme of '#AdvancesIn, ' we looked to celebrate cutting edge progress in training, clinical management, medical technology, leadership and entrepreneurialism. These updates were complimented by debates on current training in surgery and an array of focussed parallel sessions. For the first time, delegates were also able to interact with the conference digitally, with the debut of our conference smartphone App. The weekend started with 9 pre-conference courses covering a diverse range of topics including core laparoscopic, vascular, orthopaedics, neurosurgical skills, leadership and global surgery. Over 1000 abstract submissions were received and those successful competed for over 30 awards, representing nearly £4000 in trainee prizes and bursaries. As the only national surgical trainee meeting for all specialties, ASiT continues to grow and we look forward to an even larger and more successful international conference next year in Edinburgh 6–8th April 2018 with the theme of #nurturingexcellence.